Determination of Midazolam by analytical spectrophotometry - Antakli, Saad; Kabbani, Raghad; Babinsi, Haya (Journal of natural sciences, life and applied sciences, 2022)
Rapid useful and easy spectrophotometric method for the quantitative analysis of (Midazolam) (MDZ) in raw material and tablet pharmaceutical formulation has described. This method is based on the formation of yellow (ion-pair complex) between (Midazolam) and Bromocresol purple in Acetonitrile medium. Different parameters affecting the reaction such as: effect of solvents, the concentration of reagent, correlation ratio, time etc. were optimized. The formed complex was quantified spectrophotometrically at absorption maximum at 402 nm. The range of linearity was 3.26 – 26.06 µg/mL, regression analysis had a good correlation coefficient R2 = 0.9998. The limit of detection (LOD) also limit of quantification (LOQ) were 0.89 µg/mL and 2.71 µg/mL respectively. The average percent recovery was (99.46 - 100.92)% for Midazolam.This study was applied on Syrian pharmaceutical products: (DOMID-Oubari 7.5 mg). This method was successfully applied for (Midazolam) determination in tablets pharmaceutical formulation. The proposed method is direct, sensitive, simple, and doesn’t require any (extraction) process. Thus, the method could be ready to apply in routine analysis and quality control.
Keywords: Midazolam (MDZ); Benzodiazepines (BDZ); Bromocresol purple